KEY FACTORS OF CUSTOMER-SUPPLIER OF SMART MANUFACTURING IMPLEMENTATION - Ahmad, Hartini; Boukerika, Abdelhak; Shaharruddin, Sarah (International Journal of Supply Chain Management, 2019)
The paper presents a conceptual framework of the key factors of customers and suppliers in the implementation of smart manufacturing in the company. The field of the study related to competitiveness through cutting-edge technologies related to the Industrial Revolution 4.0. Hence, it shows accurate and effective decision-making in real-time from the smart manufacturing implementation. This comes together with the converging of the actual manufacturing technologies as an aid for the operations and productions. On the conceptual development, the journal articles, conference proceedings, books, dissertations, online news and newspaper, magazines related to smart manufacturing have been analyzed. A critical review creates an appropriate conceptual framework with the relationships of the key concepts of the link between customers and suppliers for the smart manufacturing implementation, as a contribution to the body of knowledge.